Gait performance and prefrontal cortex activation during single and dual task walking in older adults with different cognitive levels - Weng, Wei-Han; Yang, Yea-Ru; Yeh, Nai-Chen; Ku, Pei-Hsin; Wang, Po-Shan; Liao, Ying-Yi; Wang, Ray-Yau (Frontiers in Aging Neuroscience, 2023)
Background Growing evidence shows the cognitive function influences the motor performance. The prefrontal cortex (PFC) as a part of the executive locomotor pathway is also important for cognitive function. This study investigated the differences in motor function and brain activity among older adults with different cognitive levels, and examined the significance of cognition on motor functions. Methods Normal control (NC), individuals with mild cognitive impairment (MCI) or mild dementia (MD) were enrolled in this study. All participants received a comprehensive assessment including cognitive function, motor function, PFC activity during walking, and fear of fall. The assessment of cognitive function included general cognition, attention, executive function, memory, and visuo-spatial. The assessment of motor function included timed up and go (TUG) test, single walking (SW), and cognitive dual task walking (CDW). Results Individuals with MD had worse SW, CDW and TUG performance as compared to individuals with MCI and NC. These gait and balance performance did not differ significantly between MCI and NC. Motor functions all correlated with general cognition, attention, executive function, memory, and visuo-spatial ability. Attention ability measured by trail making test A (TMT-A) was the best predictor for TUG and gait velocity. There were no significant differences in PFC activity among three groups. Nevertheless, the PFC activated more during CDW as compared with SW in individuals with MCI (p = 0.000), which was not demonstrated in the other two groups. Conclusion MD demonstrated worse motor function as compared to NC and MCI. The greater PFC activity during CDW in MCI may be considered as a compensatory strategy for maintaining the gait performance. Motor function was related to the cognitive function, and the TMT A was the best predictor for the gait related performance in present study among older adults.